2017
DOI: 10.1002/bit.26392
|View full text |Cite
|
Sign up to set email alerts
|

NMR investigation of water diffusion in different biofilm structures

Abstract: Mass transfer in biofilms is determined by diffusion. Different mostly invasive approaches have been used to measure diffusion coefficients in biofilms, however, data on heterogeneous biomass under realistic conditions is still missing. To non-invasively elucidate fluid-structure interactions in complex multispecies biofilms pulsed field gradient-nuclear magnetic resonance (PFG-NMR) was applied to measure the water diffusion in five different types of biomass aggregates: one type of sludge flocs, two types of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 24 publications
(10 citation statements)
references
References 53 publications
1
9
0
Order By: Relevance
“…For the mobile population, self‐diffusivity of water in the granules is reduced compared to the self‐diffusivity of free water. The diffusion coefficients that were found in this study for AGS are in the same order of magnitude as the water self‐diffusion coefficients determined for different anaerobic and aerobic aggregates and biofilms (Beuling et al, 1998; Hornemann et al, 2008; Herrling et al, 2017; Lens et al, 2003, 1997; Phoenix & Holmes, 2008; Renslow, Babauta, Majors, & Beyenal, 2013; Renslow et al, 2010; Vogt, Flemming, & Veeman, 2000).…”
Section: Discussionsupporting
confidence: 83%
See 2 more Smart Citations
“…For the mobile population, self‐diffusivity of water in the granules is reduced compared to the self‐diffusivity of free water. The diffusion coefficients that were found in this study for AGS are in the same order of magnitude as the water self‐diffusion coefficients determined for different anaerobic and aerobic aggregates and biofilms (Beuling et al, 1998; Hornemann et al, 2008; Herrling et al, 2017; Lens et al, 2003, 1997; Phoenix & Holmes, 2008; Renslow, Babauta, Majors, & Beyenal, 2013; Renslow et al, 2010; Vogt, Flemming, & Veeman, 2000).…”
Section: Discussionsupporting
confidence: 83%
“…In line with the observations in the present study, Phoenix and Holmes (2008) reported relatively little diffusion heterogeneity for a structurally complex phototrophic biofilm. Furthermore, Herrling et al (2017) found there was no clear relation between diffusion and T 2 based on a D‐ T 2 experiment. Thus, T 2 maps are of limited use for the characterization of diffusional properties, despite being relatively easy to obtain.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Because mass transfer is limited in biofilms (26,27), a disinfectant solution takes a long time to reach the center of a biofilm. Therefore, bacteria in biofilms are protected from disinfectants and survive longer (26,(28)(29)(30). Human mucus, including sputum, is a viscoelastic substance that shares physical properties with biofilms (31).…”
mentioning
confidence: 99%
“…Existing research studies have mainly focused on biofilm structure, transport of water (i.e. diffusion and flow) and transport of metal ions in and around biofilms structures (Bartacek et al, 2016;Herrling et al, 2017;Manz et al, 2005;Phoenix & Holmes, 2008;Ramanan et al, 2010;Seymour et al, 2004;Wieland et al, 2001), and grown on carriers, even with complex geometry (Graf von der Schulenburg et al, 2008;Herrling et al, 2015Herrling et al, , 2017. Specifically, MRI research on biofilm growth on electrodes has revealed information about diffusion coefficients and metabolic activity (i.e.…”
Section: Chaptermentioning
confidence: 99%